NEW PELECYPODS FROM THE PALEOGENE OF UKRAINE - Berezovsky A.A. (My University, 2002)
Two new species and one new subspecies of the family Arcidae, i.e., Arca parita, A. nefanda, and A. conformis mandrikovkaensis, from the Paleogene deposits of Ukraine, are described. Several new species of the families Parallelodontidae, i.e., Porterius mira and P. promptus, and Chamidae, i.e., Chama petala and C. deplanata, are described.
Keywords: Paleogene; Cenozoic::Paleogene; Кайнозой::Палеоген